2010
DOI: 10.1186/1758-5996-2-40
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and metabolic syndrome in 7-9 years-old Portuguese schoolchildren

Abstract: BackgroundBody fat is related to changes in lipid profile, blood pressure and metabolism of insulin and glucose, known as the metabolic syndrome (MS). The aim of this study was to estimate the prevalence of metabolic syndrome (MS) and its components among overweight and obese Portuguese schoolchildren, and to identify associated clinical and biochemical characteristics.MethodsA total of 82 children (14 overweight and 68 obese; 40 boys and 42 girls) aged 7-9 years, underwent anthropometric measurements. A blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
1
12

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 34 publications
8
29
1
12
Order By: Relevance
“…Papoutsakis and cols., using the IDF definition of MS in a cohort of 1,138 healthy subjects (normal-weight, overweight, and obese) with a mean age of 11.2 years, demonstrated that leptin is a predictor of the number of metabolic syndrome components present (27). Pedrosa and cols., using the definition of MS proposed by the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP-III), showed that presence of the syndrome was associated with high leptin levels in overweight and obese children aged 7 to 9 years (28).…”
Section: Discussionmentioning
confidence: 99%
“…Papoutsakis and cols., using the IDF definition of MS in a cohort of 1,138 healthy subjects (normal-weight, overweight, and obese) with a mean age of 11.2 years, demonstrated that leptin is a predictor of the number of metabolic syndrome components present (27). Pedrosa and cols., using the definition of MS proposed by the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP-III), showed that presence of the syndrome was associated with high leptin levels in overweight and obese children aged 7 to 9 years (28).…”
Section: Discussionmentioning
confidence: 99%
“…Tal fato foi confirmado no presente estudo, sendo que essa variável foi a que apresentou menores proporções para os três critérios, 7,4% para a IDF e 1,7% para cada um dos demais critérios. Baixa proporção de GJ elevada, em estudos com crianças e adolescentes obesos, é comum na literatura 9,12,27 .…”
Section: Discussionunclassified
“…A associação entre a obesidade em populações pediátricas e a presença de fatores de risco para a síndrome metabólica, conforme observado no presente estudo, tem sido amplamente demonstrada 3,27,[30][31][32] .…”
Section: Tabela 4 -unclassified
“…Furthermore, obesity was associated with several cardiovascular risk factors in Portuguese children 40 . A Portuguese study comprising 1,433 children (6-12 yrs) highlighted that the overweight and obese prevalence was 22.3% and 10.7%, respectively, and abdominal obesity prevalence (WC ≥ 90th) was 7.8% 41 .…”
Section: Discussionmentioning
confidence: 99%